Assessment of drought tolerance using drought tolerance indices and their inter relationships in mustard [Brassica juncea (L.)] (Journal of Oilseed Brassica, 2026)
Drought is the most significant constraint for crop production which limits plant growth and production of field crops more than any other environmental stress. In order to assess drought tolerance among twenty five diverse mustard genotypes using yield based drought tolerance indices, two pot culture experiments were conducted in completely randomized design with three replications each at CSK HPKV, Palampur during rabi, 2013-14. Both experiments differed in respect of irrigation regimes. Moisture stress was created by stopping irrigation after establishment of plants from branch initiation stage to siliqua formation stage. The analysis of variance under drought stress environment revealed the significance of mean squares due to genotypes for all components except number of primary branches per plant and seeds per siliqua. Likewise, analysis of variance under non stress environment revealed the significance of mean squares due to genotypes for all parameters except days to 75% maturity, siliqua length and seeds per siliqua. The genotypes;PusaJaikisan and 03-456 exhibited highest seed yield per plant (g) in drought stress and non stress environments, respectively. Based upon drought tolerance indices such as Tolerance Index (TOL), Mean Productivity (MP),Geometric Mean Productivity (GMP),Yield Stability Index (YSI), Stress Susceptibility Index (SSI), Stress Tolerance Index (STI) and Modified Stress Tolerance Indices (K1 STI and K2 STI), PusaJaikisan appeared to be the most drought tolerant cultivaras it recorded the highest average ranksince the yield under drought stress and non stress conditions remained the same. Yield under non stress (YP ) environment showed positive and significant associations with SSI, STI, TOL, MP, GMP and K1 STI whereas significant negative association was recorded with YSI. Yield under drought stress (YS ) environment recorded positive and significant associations with STI, MP, GMP, YSI and K2 STIwhereas significant negative correlation was observed with SSI and TOL. Indices such as STI, MP and GMP could therefore, be used to select droughttolerantgenotypes with high yield performance under both drought stress andnonstress conditions.